2023
DOI: 10.1021/acs.energyfuels.2c03513
|View full text |Cite
|
Sign up to set email alerts
|

Stable Engineered Trimetallic Oxide Scaffold as a Catalyst for Enhanced Solvent-Free Conversion of CO2 into Value-Added Products

Abstract: This work demonstrates the development of mesoporous trimetallic oxide scaffolds (TOSs) as heterogeneous catalysts for the solvent-free transformation of CO2 into various value-added products. The TOS catalyst was prepared using a solution-combustion protocol as a time- and energy-saving method using cobalt, magnesium, and cerium metal nitrate salts as precursors and ethylene glycol as the fuel system and compared with their monometallic counterparts. Characterization suggested strong metal–metal and metal–oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 78 publications
(237 reference statements)
0
33
0
Order By: Relevance
“…As mentioned in Table , Comparing different metal ratios of trimetallic, bimetallic, and monometallic oxide catalysts for CO 2 fixation, the PTOF trimetallic catalyst achieved excellent results under optimized reaction conditions. Earlier reports well emphasized that the catalysts containing mixed metal oxide phases and related systems showed efficient potential for the catalytic activity . Wang et al reported that abundant multimixed metal oxide phases and their surface showed excellent catalytic activity than the bimetallic and monometallic oxide counterparts toward catalytic transformation .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned in Table , Comparing different metal ratios of trimetallic, bimetallic, and monometallic oxide catalysts for CO 2 fixation, the PTOF trimetallic catalyst achieved excellent results under optimized reaction conditions. Earlier reports well emphasized that the catalysts containing mixed metal oxide phases and related systems showed efficient potential for the catalytic activity . Wang et al reported that abundant multimixed metal oxide phases and their surface showed excellent catalytic activity than the bimetallic and monometallic oxide counterparts toward catalytic transformation .…”
Section: Resultsmentioning
confidence: 99%
“…Earlier reports well emphasized that the catalysts containing mixed metal oxide phases and related systems showed efficient potential for the catalytic activity. 29 Wang et al reported that abundant multimixed metal oxide phases and their surface showed excellent catalytic activity than the bimetallic and monometallic oxide counterparts toward catalytic transformation. 56 Remarkably, the mixed metal oxide catalytic systems will attain a more synergistic effect compared to the bimetallic and monometallic oxides under suitable reaction conditions.…”
Section: Catalytic Evaluation Of the Ptof Catalyst Inmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 2 (30−32), images are observed of more aggregation of particles with the reduction of surface smoothness. Hence, the CC-MgO surface is observed to exhibit a higher particle aggregation with irregular nanoflake morphology, as shown in Figure 2 (32). From this in-depth discussion, it is observed that precipitating agents significantly played a very decisive role to obtain uniform 3D microsphere morphology of MgO materials.…”
Section: Fe-sem Analysismentioning
confidence: 78%